Design and multi-body dynamic analysis of the Archimede space exploration rover. (May 2022) - Caruso, Matteo; Bregant, Luigi; Gallina, Paolo; Seriani, Stefano
Abstract: In this work we present the novel planetary rover prototype "Archimede". The rover is a four wheel steering vehicle where each wheel is connected to the chassis by means of an articulated leg. These also act as a suspension system, exploiting the function of complex elastic joints named S-Structures, a series of preloaded components constituting the elastic joints. These aggregates have shown to be capable of providing compliance to otherwise stiff structures. The Kane's method is used to derive an analytical model for the dynamics of the rover, treated as a multi-body system. In the model we implement a lumped-parameters model for the S-Structure as a revolute joint with an applied non-linear torque. The soil is modeled as a rigid body and the wheel–soil interaction follows the Kelvin–Voigt model. The analytical model is validated numerically – via comparison with MSC Adams simulation software – in case of ground impact and obstacle negotiation; the experimental validation is performed on ground impact tests with a Motion Amplification high speed camera and dedicated image processing software. Results show good adherence between the models, thus validating the approach. Highlights: The design of a novel planetary rover is presented, and its dynamic model derived. Legs articulated with s-structures device provide the rover of a suspension system. Small, light and compliant rover allows greater operating speed. Behavior of the rover evaluated for two different cases: drop and drive tests. Experimental results show good adherence with the simulated ones.